SYNTHESIS, SPECTRAL CHARCTERISATION AND ANTIMICROBIAL ACTIVITIES OF Cu (II), Co (II), Cr (III), COMPLEXES DERIVED FORM 4-AMINOANTIPYRINE AND DIHYDROPYRIMIDINONE OF BENZALDEHYDE - D.MOHANAMBAL; S. ARULANTONY (International Journal of Pharma and Bio Sciences, 2014)
A new series of transition metal complexes Cr (III), Co (II), and Cu (II) were synthesized from the Schiff base ligand derived from 4-aminoantipyrine and Ethyl 4- methyl –oxo-6-phenylhexahyro pyrimidine-5-carboxylate. The structural features were derived and confirmed by elemental analysis, melting point, molar conductance, Mass, Uv-Vis, FTIR, 1H-NMR, 1C-NMR, and ESR spectroscopy. The data supported that the complexes have the composition of ML2 type. The Uv-Vis, magnetic susceptibility and ESR spectral data of the complexes suggest that, the square-planar geometry around the central metal ion co-ordination through the ring carbonyl oxygen and nitrogen atom of the azomethine –C=N group. The antimicrobial screening tests were recorded by the disc diffusion method, proving more activity complexes as compared to free ligand.